2021
DOI: 10.1128/jvi.02413-20
|View full text |Cite
|
Sign up to set email alerts
|

Infection of Bronchial Epithelial Cells by the Human Adenoviruses A12, B3, and C2 Differently Regulates the Innate Antiviral Effector APOBEC3B

Abstract: Human adenoviruses (HAdVs) are a large family of DNA viruses counting more than 100 genotypes divided into seven species (A–G) and inducing respiratory tract infections, gastroenteritis and conjunctivitis. Genetically modified adenoviruses are also used as vaccines, gene therapies and anti-cancer treatments. The APOBEC3s are a family of cytidine deaminases that restrict viruses by introducing mutations in their genomes. Viruses developed different strategies to cope with the APOBEC3 selection pressure but noth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 92 publications
0
9
0
Order By: Relevance
“…The selective amplification of viral sequences carrying strand-coordinated clustered C to T mutations was performed by 3DPCR (Differential DNA Denaturation). We have previously reported that adenoviruses bear an A3 evolutionary footprint [ 21 , 22 ]. We designed 3DPCR reactions on 3 different sections of the viral genome: at the ends (E1B and E4 genes) and in the middle (L3 gene) of the linear genome.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The selective amplification of viral sequences carrying strand-coordinated clustered C to T mutations was performed by 3DPCR (Differential DNA Denaturation). We have previously reported that adenoviruses bear an A3 evolutionary footprint [ 21 , 22 ]. We designed 3DPCR reactions on 3 different sections of the viral genome: at the ends (E1B and E4 genes) and in the middle (L3 gene) of the linear genome.…”
Section: Resultsmentioning
confidence: 99%
“…We choose to tackle that question by looking at the genomic sequences of adenoviruses. We have previously reported that the A12 strain bears a stronger APOBEC3 footprint than the B3 and C2 strains [ 22 ]. We now wondered whether the A12 was the sole strain showing such footprint or whether it is shared by other adenoviruses.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations